PEMBELAJARAN KOOPERATIF SEBAGAI STRATEGI MENINGKATKAN KETERLIBATAN DAN RESPONS MAHASISWA - R, Raudiyah Rizki; Asrul, Asrul; Syarifuddin, Syarifuddin (MUST: Journal of Mathematics Education, Science and Technology, 2025)
This study aims to provide an overview of student engagement and response during mathematics learning strategy lectures using cooperative learning. The research method used is qualitative, involving 20 students randomly selected from the Mathematics Education program at UIN Sumatera Utara Medan in 2023. Analysis of student engagement was conducted based on observations, questionnaires, and interviews. The results showed that cooperative learning has a positive impact on student engagement and response, with 65% of students showing a good response and an average score of 86.14. This study identified positive academic responses, marked by the creation of new ideas from students' experiences, improved high-level thinking skills, enhanced communication skills, and social skills such as appreciating peers' opinions, exchanging ideas, and teaching acceptance of divers